Post-storm damage surveys of tornado hazards in Canada: Implications for mitigation and policy. (September 2015) - Harrison, Sara; Silver, Amber; Doberstein, Brent
Abstract: Tornadoes have the potential to cause significant destruction and loss of life in many regions across Canada. Accordingly, these hazards are essential to consider for a comprehensive emergency management plan. Following a suspected tornadic event, damage surveys are conducted by Environment Canada to determine the extent and severity of damage in order to assign an Enhanced Fujita scale rating. The purpose of this paper is to investigate the process involved in conducting storm damage surveys, and to assess how information gathered during these surveys is used. Primary research for this study involved conducting semi-structured interviews with Environment Canada damage surveyors from various provinces ( n =10) and wind engineering researchers from a large public university in Canada ( n =2), as well as an onsite observation of a damage survey conducted in Angus, Ontario after a tornado struck on 17 June 2014. The results of this study underscored the subtle but important differences between storm damage surveys conducted in the United States and Canada. It was also found that the majority of damage surveys are now conducted remotely through photos, videos, and telephone interviews with key witnesses. Finally, damage surveys were found to be a critical component of the disaster management cycle by contributing to both risk reduction and preparedness. Introducing sophisticated technologies such as mobile devices and applications, as well as using volunteered geographic information to display damage reports on a web-map, could further improve the damage surveying process in both Canada and abroad.